FAMILY LAW ISSUES IN THE CASE OF POSTHUMOUS REPRODUCTION - Samardžić, Sandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
The possibility of freezing genetic material and the production of embryos in vitro, has create the possibility of new forms of assisted reproduction. In fact, today it is possible to use genetic material and get children after the death of the person from whom the genetic material originates. This procedure causes a lot of ethical and legal questions that must be answered always bearing in mind the best interest of the child. There are various reasons that create the desire to surviving partner to use frozen materials, and that reasons can certainly affect the well-being of the child. In order to prevent negative effects of post-mortem fertilization as far as possible, this procedure should be allowed only in exceptional cases, upon the fulfillment of certain, strict set of conditions.
Keywords: the best interests of the child; posthumous reproduction; parentage